Cobalt/Manganese Oxides as Theragnosis Nanoplatforms With Magnetic Resonance/Near-Infrared Imaging for Efficient Photothermal Therapy of Tumors - Liu, Jichun; Wu, Genfa; Tang, Zhiyong; Sun, Qi; Wu, Jianxin; Lv, Renfa (Frontiers in Materials, 2019)
The combination of near-infrared (NIR) response and imaging response is a hot research area in which the functions of nanomaterials are maximized. However, the types of such materials reported so far present problems such as requiring complex synthesis. In this study, hydrophilic, porous, and hollow cobalt/manganese oxide (CMO) nanocrystals (NCs) were successfully prepared via a facile and green hydrothermal route. The CMO NCs show strong near-infrared (NIR) absorption, which results from their defect structure due to the coexistence of Co2+ and Co3+ in the as-prepared CMO NCs. Thus, the CMO NCs exhibit excellent photothermal performance, showing photothermal efficiency of up to 43.2%. In addition, the CMO NCs possess good magnetic resonance (MR) imaging performance, with longitudinal relaxivity (r1) of up to 3.48 mM−1 s−1. Finally, for the first time, we prove that the CMO nanocrystals are a promising photothermal agent. Our work provides insights into the application of Mn-based control agents and photothermal agents for photothermal theragnosis therapy.